Who pays you to be green? How customers' environmental practices affect the sales benefits of suppliers' environmental practices - Chen, Chien-Ming (2021)
This article examines whether a supplier's sales from a customer depends on the supplier's engagement in pro-environmental practices (PEPs), and how this relationship is moderated by the customer's PEP level. This article synthesizes findings from several streams of literature including corporate environmental management, supply chain management, and contingency theory. We hypothesize that (1) a supplier gets greater sales benefits from its PEPs when the (corporate) customer's PEP level is higher, and (2) a supplier gets higher sales from a customer when the supplier's PEP level aligns with the customer's PEP level. To test the hypotheses, we use data from public U.S. manufacturing firms and their key customers between 2006 and 2016. The results show that the effect of a manufacturer's PEPs on sales is significantly higher when the customer's PEP level is higher. The results also show that a manufacturer's sales from a particular customer are higher when the manufacturer's PEP level does not exceed the customers' PEP level. This study provides empirical evidence that an investment in PEPs does not always enhance sales—the sales effect of PEPs may vary according to the customer's PEP level. To our knowledge, this is the first large-scale study that examines the effect of environmental practices on sales.